COVID-19 Vaccination Uptake Among a Nationwide Sample of People Living With HIV During the Early Phase of Vaccine Rollout in China - Yang, Jianzhou; Yu, Maohe; Fu, Gengfeng; Lan, Guanghua; Li, Linghua; Qiao, Ying; Zhao, Jin; Qian, Han-Zhu; Zhang, Xiangjun; Liu, Xinchao; Jin, Xia; Chen, Guohong; et al. (Frontiers in Medicine, 2022)
People living with HIV (PLWH) are at higher risk of hospitalization and mortality caused by Coronavirus Disease 2019 (COVID-19). They are considered as a priority group to receive COVID-19 vaccination. This cross-sectional online survey investigated the prevalence of and factors associated with COVID-19 vaccination uptake among a national sample of 2740 PLWH aged 18-65 years in eight Chinese metropolitan cities between January and February 2021. As validated by requesting participants sending an image of receipt hiding personal identification, 6.2% of PLWH had taken up COVID-19 vaccination. Participants living in cities where individuals could make appointment to receive COVID-19 vaccination reported significantly higher uptake than those living in cities without such allowance (11.0% versus 2.9%, p<0.001). Being a member of priority groups to receive vaccination, having negative attitudes toward COVID-19 vaccination, and exposing to information on Internet/social media supporting PLWH to receive COVID-19 vaccination were significantly associated with COVID-19 vaccination uptake in both groups of participants. Receiving advices from staff of community-based organization supporting COVID-19 vaccination was associated with higher uptake among participants living in cities where individuals could make an appointment to receive such vaccination, while shortage in COVID-19 vaccine supply was associated with a lower uptake among participants living in other cities. Our findings presented a snapshot of COVID-19 vaccination uptake among PLWH in the early phase of vaccine rollout in China. It provided a knowledge basis to formulate interventions promoting COVID-19 vaccination for PLWH.